Febrile Convulsions - Bajaj, N (Journal of Nepal Paediatric Society, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Febrile convulsions are seizures that occur in association with fever but without evidence of intracranial infection or other definable cause in children in the age between 6 months to 5 years. Febrile convulsions have a strong genetic predisposition and a benign outcome in the majority. Febrile convulsions are clinically distinguishable as simple febrile convulsions or they are called complex febrile convulsions when they have focal features and /or are prolonged and/or recurrent in the same illness. Complex febrile convulsions are associated with higher risk of developing subsequent epilepsy. The condition of mesial temporal lobe sclerosis has been linked to prolonged febrile convulsions in childhood. Majority of febrile convulsions need only parental assurance. In few cases intermittent or continuous prophylaxis with antiepileptic drugs may have to be advised. DOI = 10.3126/jnps.v28i1.1403 J. Nepal Paediatr. Soc. Vol.28(1) p.23-26